2011
DOI: 10.1093/rheumatology/ker265
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic manifestations in giant cell arteritis are associated with area level socio-economic deprivation, but not cardiovascular risk factors

Abstract: In GCA, area-level socio-economic deprivation was associated with ischaemic manifestations: this was not mediated by traditional cardiovascular risk factors. These findings are novel and require replication. Delay between first symptoms and treatment may play a role. Public awareness campaigns about GCA should aim especially to engage individuals living in more deprived areas to encourage early presentation and prompt treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…This was an attractive suggestion given that aspirin has theoretical anti-inflammatory benefits in GCA, based on findings from a mouse model 82. Another retrospective study had similar findings,83 but other retrospective studies found the opposite84 or no effect 85 86. There may be many confounders obscuring the true association.…”
Section: Gca and Pmr: Two Diseases Or One?mentioning
confidence: 90%
“…This was an attractive suggestion given that aspirin has theoretical anti-inflammatory benefits in GCA, based on findings from a mouse model 82. Another retrospective study had similar findings,83 but other retrospective studies found the opposite84 or no effect 85 86. There may be many confounders obscuring the true association.…”
Section: Gca and Pmr: Two Diseases Or One?mentioning
confidence: 90%
“…In contrast, a study of 245 GCA and non-GCA subjects from Minnesota, United States, reported no increase in acute coronary syndrome and a lower frequency of cardiovascular risk factors at diagnosis in GCA patients (15). In addition, a study of 271 patients from the UK demonstrated no associations with pre-existing hypertension or atherosclerosis, but did find an association with social deprivation, with an OR of 4.2 (95% CI 1.3 to 13.6) for a severe ischaemic manifestation, between the most and least deprived quintiles (12). Social deprivation is an emerging risk factor for cardiovascular and cerebrovascular disease in the general population (16), probably mediated by neighborhood deprivation, smoking, physical inactivity and obesity (17,18) or inequalities in pharmacotherapy (19).…”
Section: Introductionmentioning
confidence: 94%
“…Smoking is known to increase the likelihood of developing GCA (11). An association between baseline cardiovascular risk factors and severe ischaemic events at the time of diagnosis could provide clues as to the development of later cardiovascular or cerebrovascular disease, but this link is debated (12). A study of 210 Spanish patients with GCA found an increased risk of a severe ischaemic event (defined as a composite endpoint including visual manifestations, claudication of the tongue and jaw, and cerebrovascular accidents) with every conventional cardiovascular risk factor (one of either hypertension, hyperlipidemia, smoking or diabetes), with an odds ratio (OR) of 1.79 (95%CI 1.03 to 3.11)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Delay in recognition may be the most important factor, given that the mean time from symptom onset to diagnosis of giant cell arteritis was 35 days in the study by Ezeonyeji et al, and recognition of ischemic symptoms was slow. 12 Mackie et al found that socioeconomic deprivation may be associated with ischemic complications, 15 again suggesting that lack of awareness and delay in recognition may be contributory factors.…”
Section: Predictors Of Visual Loss and Delay In Recognition: "Symptommentioning
confidence: 99%